Metal cations promote α-dicarbonyl formation in glucose-containing peritoneal dialysis fluids. - Gensberger-Reigl, Sabrina; Auditore, Andrea; Huppert, Jochen; Pischetsrieder, Monika (Glycoconjugate Journal, 2021)
Heat sterilization of peritoneal dialysis fluids (PDFs) leads to the formation of glucose degradation products (GDPs), which impair long-term peritoneal dialysis. The current study investigated the effects of metal ions, which occur as trace impurities in the fluids, on the formation of six major α-dicarbonyl GDPs, namely glucosone, glyoxal, methylglyoxal, 3-deoxyglucosone, 3-deoxygalactosone, and 3,4-dideoxyglucosone-3-ene. The chelation of metal ions by 2-[bis[2-[bis(carboxymethyl)amino]ethyl]amino]acetic acid (DTPA) during sterilization significantly decreased the total GDP content (585 μM vs. 672 μM), mainly due to the decrease of the glucose-oxidation products glucosone (14 μM vs. 61 μM) and glyoxal (3 μM vs. 11 μM), but also of methylglyoxal (14 μM vs. 31 μM). The glucose-dehydration products 3-deoxyglucosone, 3-deoxygalactosone, and 3,4-dideoxyglucosone-3-ene were not significantly affected by chelation of metal ions. Additionally, PDFs were spiked with eleven different metal ions, which were detected as traces in commercial PDFs, to investigate their influence on GDP formation during heat sterilization. Iron(II), manganese(II), and chromium(III) had the highest impact increasing the formation of glucosone (1.2-1.5 fold increase) and glyoxal (1.3-1.5 fold increase). Nickel(II) and vanadium(III) further promoted the formation of glyoxal (1.3 fold increase). The increase of the pH value of the PDFs from pH 5.5 to a physiological pH of 7.5 resulted in a decreased formation of total GDPs (672 μM vs 637 μM). These results indicate that the adjustment of metal ions and the pH value may be a strategy to further decrease the content of GDPs in PDFs.
Keywords: Glucose degradation products (GDPs); alpha-Dicarbonyls; Peritoneal dialysis fluid; Metal cations